1996
DOI: 10.1002/(sici)1098-2264(199604)15:4<234::aid-gcc5>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic hybridization reveals a specific pattern of chromosomal gains and losses during the genesis of colorectal tumors

Abstract: Comparative genomic hybridization was used to screen the DNA extracted from histologically defined tissue sections from consecutive stages of colorectal carcinogenesis for chromosomal aberrations. No aberrations were detected in normal epithelium (n = 14). Gain of chromosome 7 occurred as a single event in low-grade adenomas (n = 14). In high-grade adenomas (n = 12), and overrepresentation of chromosomes 7 and 20 was present in 30% of the cases analyzed. The transition to colon carcinomas (n = 16) was characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
72
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 0 publications
19
72
2
Order By: Relevance
“…Overall, the chromosomal aberrations described here are consistent with chromosomal changes previously reported for colorectal cancer. [10][11][12][13] Although the number of genomic aberrations may potentially substitute for chromosomal instability, it was paramount to establish the MSI status of the tumours because it could have had a profound impact on the analysis of disease-free survival. It is well established that cancers with high microsatellite instability have better survival than microsatellite stable tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the chromosomal aberrations described here are consistent with chromosomal changes previously reported for colorectal cancer. [10][11][12][13] Although the number of genomic aberrations may potentially substitute for chromosomal instability, it was paramount to establish the MSI status of the tumours because it could have had a profound impact on the analysis of disease-free survival. It is well established that cancers with high microsatellite instability have better survival than microsatellite stable tumours.…”
Section: Discussionmentioning
confidence: 99%
“…5 Cytogenetic and molecular cytogenetic analyses have revealed that tumor-specific gains and losses of entire chromosomes or chromosome arms are early genome mutations. [6][7][8][9] The genomic imbalances show a strikingly conserved recurrent pattern that is characteristic for colorectal carcinomas and is distinct from other solid tumors. 6 For a comprehensive overview, please see http://cgap.…”
mentioning
confidence: 99%
“…[21][22][23][24] CGH studies on both colorectal adenomas and carcinomas have also confirmed the gain of chromosome 7 material as a frequent change. 11,12,25,26 Ried et al 12 demonstrated gain of chromosome 7 material in 4 of 12 in what they described as high-grade adenomas. The neoplasia-specificity of ϩ7 has been questioned, however, both in the context of colorectal carcinogenesis and in general.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) analyses of colorectal adenomas have demonstrated increased chromosome material in the same 3 chromosomes, also reflecting that it must be an in vivo phenomenon. 11,12 Three copies of chromosome 7 were identified in 16 of the cases analyzed (34%). When compared with the chromosome 1 copy number in each case, additional copies of chromosome 7 were found in 15 adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation